2019
DOI: 10.1167/iovs.19-26936
|View full text |Cite
|
Sign up to set email alerts
|

Apratoxin S4 Inspired by a Marine Natural Product, a New Treatment Option for Ocular Angiogenic Diseases

Abstract: Citation: Qiu B, Tan A, Veluchamy AB, et al. Apratoxin S4 inspired by a marine natural product, a new treatment option for ocular angiogenic diseases. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…We have recently shown that apratoxin S4 strongly inhibits retinal vascular cell activation by suppressing several angiogenic pathways ( Qiu et al., 2019 ). It was shown to act on retinal endothelial cells as well as pericytes and has the potential to overcome drug resistance to anti-VEGF therapy through its unique mechanism of action ( Qiu et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that apratoxin S4 strongly inhibits retinal vascular cell activation by suppressing several angiogenic pathways ( Qiu et al., 2019 ). It was shown to act on retinal endothelial cells as well as pericytes and has the potential to overcome drug resistance to anti-VEGF therapy through its unique mechanism of action ( Qiu et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the preclinical candidate apratoxin S10 exerted activity against cancer cells derived from highly vascularized tumors with 2000–5000 times greater potency than standard RTK inhibitors and also displayed antiangiogenic activity, in addition to its inherent anticancer properties ( Cai et al., 2017 ). Due to the unique mechanism, inhibiting VEGF secretion and downregulating other proangiogenic factors and receptors, apratoxin S4 was recently “repurposed” and shown to be highly effective in inhibiting ocular angiogenesis, and specifically pathological neovascularization, in organoids, rabbit and mouse models, and acting on retinal endothelial cells as well as pericytes ( Qiu et al., 2019 ). These data suggest that apratoxin S4 is also a treatment option to prevent blindness, even for populations that are resistant to anti-VEGF (standard-of-care) therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Decapterus tabl ingredients could significantly inhibit retinal neovascular tufts by inhibiting HIF expression in the oxygen-induced retinopathy (OIR) mouse model [ 39 ]. Apratoxin S4, derived from a marine cyanobacterial compound, exhibits potent anti-angiogenic effects in OIR mouse models, a mouse model of laser-induced choroidal neovascularization, and persistent retinal neovascularization rabbit model through mediating multiple angiogenic pathways [ 19 ]. Largazole was identified as one of the marine cyanobacteria metabolites with a novel chemical structure from a cyanobacterium of the genus Symploca and later reclassified as Caldora penicillata [ 20 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, more than 25,700 compounds with unique chemical structures have been extracted from marine organisms, like molluscs, soft corals, fishes, and many microorganisms [ 18 ]. We recently described a marine natural product inspired inhibitor of cotranslational translocation, Apratoxin S4, as a potent anti-angiogenic compound in vitro and ex vivo and as an inhibitor of pathological ocular neovascularization in vivo [ 19 ]. The cyclodepsipeptide Largazole, isolated from a marine cyanobacterium, has been shown to have potent anti-proliferative properties in multiple cancer cell lines by inhibiting class I histone deacetylases (HDACs) [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ap ra t ox i n E ( 55 ) Further studies on apratoxin S4 (50), revealed the molecule to possess potent antiangiogenic activity by inhibiting the activation of retinal endothelial cells and pericytes through mediating multiple angiogenic pathways [125]. This finding could path the way for the development of apratoxin S4 as a potential cure for prevention or treatment of vision loss.…”
Section: Apratoxin Amentioning
confidence: 99%